An Investigation of Consumption and Identity of Students in Beijing in the Luxury Goods Marketplace, Comparing with that of Chinese Students in the UK - TANG, JING (2013)
Purpose— With the incredible economy growth of China, the number of the China’s middle class members are increasing and thus luxury consumption in China is growing too. China has become the largest luxury products consumer in the world now. Understanding Chinese consumers’ luxury consumption behaviour is essential to managers. However, among massive consumers who have great purchase power, university students are easier to be attracted by luxury products. As the most potential group consumers for luxury brand, studying students’ luxury consumption and identity are also necessary and important for managers and academic researchers. Therefore, this research is going to investigate consumption and identity of students in Beijing in the luxury goods marketplace and compares with that of Chinese students in the UK.